N-Aryl mercaptoacetamides as potential multi-target inhibitors of metallo-β-lactamases (MBLs) and the virulence factor LasB from Pseudomonas aeruginosa. Issue 10 (23rd August 2021) - Yahiaoui, Samir; Voos, Katrin; Haupenthal, Jörg; Wichelhaus, Thomas A.; Frank, Denia; Weizel, Lilia; Rotter, Marco; Brunst, Steffen; Kramer, Jan S.; Proschak, Ewgenij; Ducho, Christian; Hirsch, Anna K. H.
Abstract : Simultaneous inhibition of metallo-β-lactamases (MBLs) and virulence factors such as LasB from Pseudomonas aeruginosa offers a new approach to combat antibiotic-resistant pathogens. Abstract : Increasing antimicrobial resistance is evolving to be one of the major threats to public health. To reduce the selection pressure and thus to avoid a fast development of resistance, novel approaches aim to target bacterial virulence instead of growth. Another strategy is to restore the activity of antibiotics already in clinical use. This can be achieved by the inhibition of resistance factors such as metallo-β-lactamases (MBLs). Since MBLs can cleave almost all β-lactam antibiotics, including the "last resort" carbapenems, their inhibition is of utmost importance. Here, we report on the synthesis and in vitro evaluation of N -aryl mercaptoacetamides as inhibitors of both clinically relevant MBLs and the virulence factor LasB from Pseudomonas aeruginosa . All tested N -aryl mercaptoacetamides showed low micromolar to submicromolar activities on the tested enzymes IMP-7, NDM-1 and VIM-1. The two most promising compounds were further examined in NDM-1 expressing Klebsiella pneumoniae isolates, where they restored the full activity of imipenem. Together with their LasB-inhibitory activity in the micromolar range, this class of compounds can now serve as a starting point for a multi-target inhibitor approach against both bacterial resistance and virulence, which is unprecedented in antibacterial drug discovery.